Novelle italiane antiche nella tradizione manoscritta: contenuto, struttura e genealogia del cod. Firenze, BNCF II III 343 (Carte Romanze, 2023)
A rich corpus of Italian novelle is transmitted by a few codexes from the 14th to the 16th century, including the first printed edition published in 1525 under the apocryphal title of Le cento novelle antiche (The One Hundred Ancient Tales, namely the Vulgate Novellino), but they differ from each other in order and number of pieces. The article mainly focuses on the ms. II III 343 of the National Central Library of Florence, containing a series of Vite di filosofi (Lives of Eminent Philosophers), about fifty novelle of the Novellino and ten more short stories not attested elsewhere. The importance of this narrative collection from the 15th century is highlighted here: the ms. contains the fragment of an early version of the Novellino, but is also a remarkable anthology that assembles different collections composed by different authors and collected by the same copyst. The comparison of its sections with each other, and with the other codexes that partially share the corpus, spreads light on the laboratory of the novella, on some aspects of its written circulation in the first centuries, its definition and its developments since the ancient Libro di novelle e di bel parlar gentile (Book of Tales and of Lovely Gentle Speech) or Ur-Novellino.
Keywords: he One Hundred Ancient Tales; Book of Tales and of Lovely Gentle Speech; Manuscript tradition; Ancient collections of Italian short stories; Italian novella (13th-14th century); Ms. Firenze BNCF II III 343